Pengaruh Kualitas Pelayanan Dan Kepuasan Konsumen Terhadap Loyalitas Konsumen Di Kozzi Sintang - Yuyun Yuyun; Yasir Hudzaifah; Joko Susilo (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The objective of this research is to evaluate the influence of service quality and customer satisfaction on customer loyalty towards Kozzi Sintang. This study employs a quantitative associative approach with 100 respondents, each at least 17 years of age and having purchased Kozzi Sintang products a minimum of two times (purposive sampling). The analysis utilizes the multiple correlation coefficient (R), the coefficient of determination (R²), and the F-test. Service quality and customer satisfaction influence 17.6 percent of customer loyalty (R² = 0.176). Other factors beyond the scope of this research account for the remaining 82.4 percent of customer loyalty. The F-test indicates that service quality and customer satisfaction together have a statistically significant effect on customer loyalty (Sig. 0.000 < 0.05). Furthermore, service quality has a statistically significant individual effect (p-value 0.002 < 0.05; calculated t-statistic 3.190 > critical t-value 1.984), whereas customer satisfaction does not have a statistically significant individual effect (p-value 0.262 > 0.05; calculated t-statistic 1.128 < critical t-value 1.984).